2020
DOI: 10.12659/msm.915825
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MiR-122 Decreases Cerebral Ischemia-reperfusion Injury by Upregulating DJ-1-Phosphatase and Tensin Homologue Deleted on Chromosome 10 (PTEN)/Phosphonosinol-3 Kinase (PI3K)/AKT

Abstract: Departmental sources Background: Ischemia-reperfusion injury is caused by a blood reperfusion injury in ischemic brain tissue, and usually occurs in the treatment stage of ischemic disease, which can aggravate brain tissue injury. MiR-122 is closely related to ischemia-reperfusion injury in the myocardium, kidney, and liver; however, the role in cerebral ischemiareperfusion injury has not been established. Material/Methods: In this study, cerebral ischemia-reperfusion injury was established in a rat model, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Nonetheless, it is worth mentioning that confounding results have been obtained concerning the modulation of DJ-1 expression levels upon IR. Indeed, while some studies have reported an increased DJ-1 expression [ 24 , [144] , [145] , [146] ], other groups have observed no change [ 142 , 147 ] or even a decreased expression level [ 148 , 149 ]. As these discrepancies may be attributable to different models, experimental procedures, or time windows considered, more studies should be performed to elucidate whether and how DJ-1 expression is transcriptionally regulated under this condition.…”
Section: The Involvement Of Dj-1 In Ir Injurymentioning
confidence: 99%
“…Nonetheless, it is worth mentioning that confounding results have been obtained concerning the modulation of DJ-1 expression levels upon IR. Indeed, while some studies have reported an increased DJ-1 expression [ 24 , [144] , [145] , [146] ], other groups have observed no change [ 142 , 147 ] or even a decreased expression level [ 148 , 149 ]. As these discrepancies may be attributable to different models, experimental procedures, or time windows considered, more studies should be performed to elucidate whether and how DJ-1 expression is transcriptionally regulated under this condition.…”
Section: The Involvement Of Dj-1 In Ir Injurymentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine are important antioxidant enzymes, which can alleviate the injury caused by oxidative stress, and the levels of ROS and MDA reflect the degree of lipid peroxidation in cells and tissues [27][28][29]. e results showed that electroacupuncture could reduce the levels of ROS and MDA in serum.…”
Section: Discussionmentioning
confidence: 98%
“…The higher the score, the more severe the symptoms of neural power defciency. Neurological functions were evaluated 24 h, and 3 and 7 days following MCAO/R using a modified Neurological Severity Scale (mNSS), as previously described (26). This scale includes measurement of balance, reflex, sensory and motor skills.…”
Section: Methodsmentioning
confidence: 99%